A Battle of the Norms in EU Chemicals Regulation Space: Reflections on the Court of Justice Decision on the Concept of "Articles" Under REACH. (December 2015) - Vaughan, Steven
Abstract : Judgment of the Court (Third Chamber) delivered on 10 September 2015 in Case C-106/14, Fédération des entreprises du commerce et de la distribution (FCD) and Fédération des magasins de bricolage et de l'aménagement de la maison (FMB) v Ministre de l'écologie, du développement durable et de lʼénergie.